Between the universality of Human Rights and the import/export of "Western" legal and conceptual tools in "black" Africa : Case of the Burkinabè framework for combating inequalities and discrimination against women - (:unkn) unknown (My University, 2020)
Qyestioning the universality and exportability of Human Rights implies the presupposition that they were developed in a certain socio-legal context and that they are transposed elsewhere. If we remain within the framework of a universalism posited as a dogma, Human Rights seem to know only one truth: that of the relationship of male and "white" domination; the peculiarities (being not "white"), as well as the differences (being women) are then erased. Countries in "black" Africa are exposed to an internationally defined multidimensional hierarchy. As a result, "black'' African women undergo a double domination, horizontal (for their color and for their sex), and vertical (by the dominant ones and by the other dominated ones of the chain). The common element that links these two situations is the fact that the color "black" assigns a position in the legal, social, economic, and intellectual order, establishing a relationship of coloniality maintained both by the authors and by the victims. Discriminatory colonial categorizations assume that development aid submitted to them by international institutions and "Western" states is in a perspective of co-constructing the domination assumed by both sides. The application of the universality of human rights then turns out to be problematic insofar as certain cultural, social and legal specificities are not taken into account as required by human rights.
Keywords: African Research